2022
DOI: 10.1017/s0007123422000114
|View full text |Cite
|
Sign up to set email alerts
|

Personalization of Power and Mass Uprisings in Dictatorships

Abstract: Most major nonviolent civil resistance campaigns target autocratic regimes. Yet, most dictators are toppled by their close supporters, not civilian protesters. Building on theories of strategic interactions between leaders, security agents, and protesters, we make three core claims: first, protesters are relatively less likely to mount a major nonviolent uprising against dictatorships with personalized security forces; secondly, personalized security forces are more likely to repress realized protest; and, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 80 publications
0
0
0
Order By: Relevance
“…Understanding whether the personalization of power in dictatorships is associated with growing efforts to control the masses via non-violent means has implications for research on the politics of authoritarian rule. While studies of personalism recognize that the personalization of power affects the onset and outcome of mass uprisings (e.g., Chin et al, 2023), personalist dictators' ability to manage the masses have remained poorly understood. In a similar vein, studies have suggested that in the process of amassing power, personalist leaders shut down alternative pathways of socio-political control (e.g., Davenport, 2007a).…”
Section: Indoctrinationmentioning
confidence: 99%
“…Understanding whether the personalization of power in dictatorships is associated with growing efforts to control the masses via non-violent means has implications for research on the politics of authoritarian rule. While studies of personalism recognize that the personalization of power affects the onset and outcome of mass uprisings (e.g., Chin et al, 2023), personalist dictators' ability to manage the masses have remained poorly understood. In a similar vein, studies have suggested that in the process of amassing power, personalist leaders shut down alternative pathways of socio-political control (e.g., Davenport, 2007a).…”
Section: Indoctrinationmentioning
confidence: 99%
“…OPCW's goals are to eradicate chemical weapons stocks, guarantee the nonproliferation of such weapons, help governments defend themselves from chemical weapons assaults, and encourage international collaboration in the peaceful use of chemistry. All signing governments agree to provide OPCW inspectors unrestricted access to all locations housing chemical weapons and destroy all stock of chemical weapons (Chin et al, 2022). Sites and victims of alleged chemical weapons attacks are also subjected to testing by the OPCW.…”
Section: The Chemical Weapons Convention Established the Internationalmentioning
confidence: 99%
“…The Assad regime launched a missile barrage containing sarin into the rebel-held area. This massive missile barrage's estimated death count range from 281 based on French intelligence up to 1429 based on U.S. intelligence, While the injured are estimated to be in a thousand (Bunker, 2018).…”
Section: Warmentioning
confidence: 99%
“…3 I use this concept after Thomas Kuhn's (1970) distinction between 'normal' and 'revolutionary science' in The Structure of Scientific Revolutions which pits a Whiggish view of the history of science as a long period of the steady accumulation of detail and facts versus a revolutionary phase characterized by uncertainty and anomalies that do not fit with existing theory, awaiting the next 'revolutionary' conceptual breakthrough as in the shift from classical mechanics to quantum theory. peters regimes by nonviolent civil resistance (Chin et al, 2022). Women increasingly make up resistance leaders4 and women make up a greater proportion of heads of state than at any time in the past (Peters, 2016).…”
Section: Max Weber Legitimate Authority and Charismamentioning
confidence: 99%